Anatomically Preserved Early Cretaceous Bennettitalean Leaves: Nilssoniopteris corrugata n. sp. from Vancouver Island, Canada. (September 2014) - Ray, M. Madeleine; Rothwell, Gar W.; Stockey, Ruth A.
Abstract : Early Cretaceous fossilized leaves assignable to the extinct seed plant order Bennettitales occur within an exceptionally diverse Early Cretaceous (Valanginian) flora of anatomically preserved plant fossils at Apple Bay on Vancouver Island, British Columbia, Canada. One of the bennettitalean leaf types has an entire margin, with laminae that are attached near the adaxial surface of the midvein. Leaves are 10–15 mm wide with an adaxial surface that shows distinct corrugations, and a midrib that is exposed adaxially. The vascular system of the midrib consists of a crescent-shaped ring of collateral bundles. Lateral veins diverge from midrib at ∼90°, are typically simple but occasionally branch at base of the lamina. Vein density is 12–15 per cm. Leaves are hypostomatic with syndetocheilic stomata that are randomly oriented between veins. Internal anatomy consists of an adaxial hypodermis of closely-spaced isodiametric cells, mesophyll that is differentiated into adaxial palisade and abaxial spongy zones, and collateral bundles that show a distinct bundle sheath with bundle sheath extensions. This novel combination of characters represents the diverse bennettitalean genus Nilssoniopteris. Nilssoniopteris corrugata new species is only the second species of the genus for which internal anatomy is preserved. This species increases the known variation of bennettitalean leaf anatomy, and reinforces our appreciation for the global distribution of bennettitalean seed plants during the Mesozoic.